AR and VR Training System for Children with ASD: A Detailed and Innovative Review - Huamanchahua, Deyby (2022)
Augmented Reality (AR) and Virtual Reality (VR) are emerging technologies that have increased their implementation in research. This has allowed the construction of interactive systems that have become part of modern teaching methodologies. The use of these technologies for the development of training systems provides opportunities for improvement in teaching environments, especially for children with Autism Spectrum Disorder (ASD). They require special education due to their different abilities. Previous research has developed learning systems for children with ASD with different approaches and methodologies. Thus, the present article provides a detailed review of AR/VR educational systems oriented to children with autism. We obtained 24 research papers on the topic from 2017 to 2022, which shows a lack of research works in AR and VR for special education of people with ASD.